Hamiyati Application of Case Method Model Based on Character Values in Reproductive System Materials to Improve Critical Thinking and Conation skills - Andi Ulfa Tenri Pada; Safrida Safrida; Khairil Khairil; Wiwit Artika; Hamiyati Hamiyati (Postgraduate, University of Mataram, 2022)
It is important for students to comprehend the concepts as the ability not only to understand, but also to be able to apply the concepts given to solve a problem, and to think critically about the problems during the learning process. The purpose of this study was to determine the improvement differences of students' critical thinking skills after the application of the case method model learning based on character values ​​in the reproductive system material in SMA IT Al-Fityan and SMA IT Al-Arabiyah. The research method included quasi-experimental research with a pretest-posttest non-equivalent control group design with a sample of 116 students. Data collection techniques used was students' learning outcomes data by using pretest and posttest questions in the form of multiple choices with reasons. The questions were according to the indicators that must be achieved during learning process. Then the data was analyzed by using the average value of the pretest and posttest, then the average difference test was carried out. Hypothesis testing for students' critical thinking skills was analyzed by using = 0.05 with a significant level of 0.95% with the following test criteria: If tCount < tTable then Ho is accepted, and if tCount ≥ tTable then Ho is rejected. The study results in the findings that: 1) Improvement in students' critical thinking skills by applying case method learning models based on character values ​​in reproductive system materials; 2) The character value of students was greatly improved during learning process and when students are in the environment; 3) The relation between improving critical thinking skills and character values ​​in the learning process was excellent.